2006
DOI: 10.4049/jimmunol.176.3.1860
|View full text |Cite
|
Sign up to set email alerts
|

Fraktalkine Produced by Airway Smooth Muscle Cells Contributes to Mast Cell Recruitment in Asthma

Abstract: Human airway smooth muscle cells (HASMC) secrete fractalkine (FKN), a chemokine the concentration of which is increased in asthmatic patients. HASMC also induce mast cell chemotaxis, as a component of asthma inflammation. We therefore evaluated the role of smooth muscle-derived FKN in mast cell migration. We assessed the capacity of recombinant FKN to induce human mast cell chemotaxis. This effect implicates a calcium-independent pathway involving actin reorganization and protein kinase C-δ. We found that HASM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
136
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(143 citation statements)
references
References 33 publications
2
136
0
3
Order By: Relevance
“…It is therefore likely that the migration of mast cells is under the control of several chemokines. Previous studies have demonstrated that a number of chemotactic factors such as CCL5, CCL11, CX3CL1, IL-8, IL-6 contributed to regulate the migration of human mast cells (Nilsson et al, 1999;Juremalm et al, 2002;El-Shazly et al, 2006;Hollins et al, 2008;Zweifel et al, 2010).In this study, we found that chemokines including CCL5, CCL11, CX3CL1, and IL-8 were up-regulated in the epithelial cells of nasal polyps, but IL-6 was not expressed by nasal epithelial cells. This indicated that these chemokines except for IL-6, released from epithelial cells of nasal polyps may be responsible for the migration of mast cells toward the epithelium in nasal polyps.…”
Section: Discussionsupporting
confidence: 61%
“…It is therefore likely that the migration of mast cells is under the control of several chemokines. Previous studies have demonstrated that a number of chemotactic factors such as CCL5, CCL11, CX3CL1, IL-8, IL-6 contributed to regulate the migration of human mast cells (Nilsson et al, 1999;Juremalm et al, 2002;El-Shazly et al, 2006;Hollins et al, 2008;Zweifel et al, 2010).In this study, we found that chemokines including CCL5, CCL11, CX3CL1, and IL-8 were up-regulated in the epithelial cells of nasal polyps, but IL-6 was not expressed by nasal epithelial cells. This indicated that these chemokines except for IL-6, released from epithelial cells of nasal polyps may be responsible for the migration of mast cells toward the epithelium in nasal polyps.…”
Section: Discussionsupporting
confidence: 61%
“…In many instances, asthma has an allergic component characterized by allergic sensitivity to allergens and increased serum levels of antigenspecific IgE and total IgE. The role of the mast cell in asthma is of renewed interest due to reports that mast cell numbers are increased within the airway smooth muscle bundles of asthmatic patients [20][21][22][23][24][25]. This has led to a re-evaluation of the mast cell as a crucial effector cell in the pathogenesis of asthma, especially asthma with an allergic basis.…”
Section: Asthmamentioning
confidence: 99%
“…Mast cells numbers, but not T cells or eosinophils, are increased within the airway smooth muscle (ASM) of asthmatic patients [20,21,24,25]. The location of mast cells within the ASM is believed to facilitate hyper- [26,27].…”
Section: Asthmamentioning
confidence: 99%
“…Chez l'homme, CX3CL1 est exprimée par divers types cellulaires et tissus dont les neurones [10], l'épithélium intestinal [11] et pulmonaire [12], ainsi que la peau [13], les cellules musculaires lisses pulmonaires [14] et l'endothélium ombilical [6]. Chez la souris, les principales données sur la localisation de CX3CL1 proviennent de la génération d'une lignée de souris exprimant une protéine rapporteur fluorescente comme marqueur de substitution pour l'expression de la chimiokine [15].…”
Section: Distribution Cellulaire De Cx3cl1unclassified
“…Cellesci augmentent encore après un test d'épreuve à l'allergène chez les patients allergiques asthmatiques [12]. Chez les patients asthmatiques, l'expression de la chimiokine est également augmentée dans les cellules musculaires lisses des voies aériennes, l'endothélium pulmonaire et l'épithélium bronchique suite à un test d'épreuve [14]. Dans leur ensemble, ces résultats montrent que, chez les patients allergiques, CX3CL1 est activé par clivage, vraisemblablement à la suite de l'activation d'ADAM17 (qui initie la réaction de coupure de la chimiokine).…”
Section: Distribution Cellulaire Du Récepteur Cx3cr1 En Conditions Hounclassified